2018
DOI: 10.7717/peerj.5187
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the discovery of amphipod crustaceans

Abstract: At present, amphipod crustaceans comprise 9,980 species, 1,664 genera, 444 subfamilies, and 221 families. Of these, 1,940 species (almost 20%) have been discovered within the last decade, including 18 fossil records for amphipods, which mostly occurred in Miocene amber and are probably all freshwater species. There have been more authors describing species since the 1950s and fewer species described per author since the 1860s, implying greater taxonomic effort and that it might be harder to find new amphipod s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…2b). A similar trend of an all-time peak in authors in recent decades was also observed for various taxa such as fossil mammals [19], amphibians, birds, cone snails, flowering plants, mammals and spiders [20,21], fish [22,23], Brazilian flowering plants and land vertebrates [24], parasites [25], and amphipod crustaceans [26]. The increase in the number of authors was also the case for all taxa on Earth [3].…”
Section: Discussionsupporting
confidence: 71%
“…2b). A similar trend of an all-time peak in authors in recent decades was also observed for various taxa such as fossil mammals [19], amphibians, birds, cone snails, flowering plants, mammals and spiders [20,21], fish [22,23], Brazilian flowering plants and land vertebrates [24], parasites [25], and amphipod crustaceans [26]. The increase in the number of authors was also the case for all taxa on Earth [3].…”
Section: Discussionsupporting
confidence: 71%
“…Due to their diversity and prominence in the shores of the Macaronesia, members of the amphipod family Hyalidae Bulycheva, 1957 are particularly interesting subjects to investigate the role of the NEA islands in the genetic structuring of marine invertebrates. This family currently includes 11 genera and more than 140 species worldwide (Arfianti, Wilson, & Costello, ; Horton et al, ). Members of Hyalidae are predominantly and commonly found in macroalgae canopy in the intertidal and shallow subtidal of tropical and subtropical regions (Serejo & Sittrop, ), although a few species are reported at higher latitudes (McBane & Croker, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, arguably calling those who described species as a taxonomist is an underestimate. In any case, because the proportion of these part-time or once-off taxonomists has not changed in over a century, then the fact that there are so many more authors of new species, even if only first authors are counted, represents an increased taxonomic workforce (Alroy 2002;Joppa et al 2011;Appeltans et al 2012;Costello et al 2012Costello et al , 2013dCostello et al , 2014aCostello et al , 2014bBebber et al 2014;Arfianti et al 2018;Pamungkas et al 2019;Pagès-Escolà et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the increasing numbers of publications of new species (Lohrmann et al 2012;Costello et al 2013b), there were seven times more authors of marine species in the first decade of this century than any decade before (Costello et al 2015a). Even if only first authors of new species descriptions are counted there are several times more authors now than prior to the 1960s (Arfianti et al 2018, Pamungkas et al 2019, Pagès-Escolà et al 2020. There has been a trend for more multiple authorships since the 1980s reflecting more inclusive authorship practices and more comprehensive species descriptions (Joppa et al 2011, Costello et al 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation